Design and Analysis of Three-DOF Parallel Manipulator Controlled by Cam - Ge Zhenghao; Han Xiaoyu; Wang Zhilong (Jixie chuandong)
A single-input three-DOF parallel manipulator controlled by cam is designed based on the parallel mechanism theory. And then the kinematics study is carried out,the analysis of the freedom of the manipulator is completed,the kinematic forward solutions and kinematic inverted solutions are worked out. On this basis,the parametric design of the cam is completed. Finally,by using the kinematics simulation with Pro/E,the correctness of the design is verified,the theoretical basis for the establishment of manipulator speed and acceleration model,workspace and singularity analysis is provided.